Collapsing Structures and Public Mismanagement - Seibel, Wolfgang (Springer Nature, 2022)
This open access book is about mismanagement of public agencies as a threat to life and limb. Collapsing bridges and buildings kill people and often leave many more injured. Such disasters do not happen out of the blue nor are they purely technical in nature since construction and maintenance are subject to safety regulation and enforcement by governmental agencies. This book analyses four relevant cases from Australia, New Zealand, the USA and Germany. Arguing that, while preventing disaster through public oversight is essentially easy, the difficult part for public officials and private contractors and consultants alike is to resist incentives that threaten professional skills and standards. Rather than stressing well-known pathologies of bureaucracy as a potential source of disaster, this book argues, learning for the sake of prevention should aim at neutralizing threats to integrity and strengthening a sense of responsibility among public officials.